Twin‐Structured Graphene Metamaterials with Anomalous Mechanical Properties. Issue 17 (17th March 2022) - Lin, Zaishan; Dong, Jiaqi; Wang, Xin; Huang, Qitao; Shen, Xi; Yang, Minglong; Sun, Xianxian; Yuan, Ye; Wang, Shasha; Ning, Yuanhao; Yang, Shuang; Yin, Weilong; et al.
Abstract: Typically, solid materials exhibit transverse contraction in response to stretching in the orthogonal direction and transverse expansion under compression conditions. However, when flexible graphene nanosheets are assembled into a 3D porous architecture, the orientation‐arrangement‐delivered directional deformation of micro–nanosheets may induce anomalous mechanical properties. In this study, a 3D hierarchical graphene metamaterial (GTM) with twin‐structured morphologies is assembled by manipulating the temperature gradient for ice growth during in situ freeze‐casting procedures. GTM demonstrates anomalous anisotropic compression performance with programable Poisson's ratios (PRs) and improved mechanical properties (e.g., elasticity, strength, modulus, and fatigue resistance) along different directions. Owing to the designed three‐phase deformation of 2D graphene sheets as basic microelements, the twin‐structure GTM delivers distinctive characteristics of compressive curves with an apparent stress plateau, and follows a strengthening tendency. This multiscale deformation behavior facilitates the enhancement of energy loss coefficient. In addition, a finite element theory based numerical model is established to optimize the structural design, and validate the multiscale tunable PR mechanism and oriented structural evolution. The mechanical and thermal applications of GTM indicate that the rational manipulation‐driven design of meta‐structures paves the way for exploring graphene‐based multifunctional materials with anomalous properties. Abstract : A 3D graphene metamaterial with twin‐structured morphology is constructed by orientated icing growth under manipulation of the temperature gradient, which demonstrates the anomalous physical properties, such as programable Poisson's ratio, superelasticity, and high resilience. Experimental investigation and numerical simulation cooperatively validate the triggering mechanism including oriented evolution of the hierarchical microstructure and elastic buckling of the cell walls.